-14=3(x-4)-5x

Simple and best practice solution for -14=3(x-4)-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14=3(x-4)-5x equation:



-14=3(x-4)-5x
We move all terms to the left:
-14-(3(x-4)-5x)=0
We calculate terms in parentheses: -(3(x-4)-5x), so:
3(x-4)-5x
We add all the numbers together, and all the variables
-5x+3(x-4)
We multiply parentheses
-5x+3x-12
We add all the numbers together, and all the variables
-2x-12
Back to the equation:
-(-2x-12)
We get rid of parentheses
2x+12-14=0
We add all the numbers together, and all the variables
2x-2=0
We move all terms containing x to the left, all other terms to the right
2x=2
x=2/2
x=1

See similar equations:

| 2p^2+3=3p^2 | | -8u+2(u+5)=28 | | 3+7x=4+2x | | -39=5(y-5)-7y | | 8x2+5x-3=0 | | z2+3=z4 | | 4a-11=2a-7 | | 6=13d | | 13-v=27 | | X2-8x=242 | | -7(1+n)=-n+29 | | 180=4x-15 | | -14+4m=-30 | | 12+r=25 | | 2(4x-6)=-36 | | 2-(Y+2=3y | | -4(-7a-2)=31+5a | | m=m-4 | | X2+10x=6 | | 4(x-7)=2x+46 | | x/4+26=89 | | -7(-8x+3)=189 | | 13x-22+13+8x=180 | | X2+11x=3 | | 160+10x=10x^2 | | -8y=1.44 | | 4x+6=18+7x-9 | | 17*x=289 | | 3x+89=8x+58+90 | | 3x+89=8x+58=90 | | 289/x=x | | 13x-32+7x-8=180 |

Equations solver categories